Understanding the management of early-stage chronic kidney disease in primary care: a qualitative study - Blakeman, Tom (Royal College of General Practitioners, 2012)
BACKGROUND: Primary care is recognised to have an important role in the delivery of care for people with chronic kidney disease (CKD). However, there is evidence that CKD management is currently suboptimal, with a range of practitioner concerns about its management. AIM: To explore processes underpinning the implementation of CKD management in primary care. DESIGN AND SETTING: Qualitative study in general practices participating in a chronic kidney disease collaborative undertaken as part of the National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care (CLAHRC) for Greater Manchester. METHOD: Semi-structured interviews were conducted with GPs and practice nurses (n = 21). Normalisation Process Theory provided a framework for generation and analysis of the data. RESULTS: A predominant theme was anxiety about the disclosure of early-stage CKD with patients. The tensions experienced related to identifying and discussing CKD in older people and patients with stage 3A, embedding early-stage CKD within vascular care, and the distribution of work within the practice team. Participants provided accounts of work undertaken to resolve the difficulties encountered, with efforts having tended to focus on reassuring patients. Analysis also highlighted how anxiety surrounding disclosure influenced, and was shaped by, the organisation of care for people with CKD and associated long-term conditions. CONCLUSION: Offering reassurance alone may be of limited benefit, and current management of early-stage CKD in primary care may miss opportunities to address susceptibility to kidney injury, improve self-management of vascular conditions, and improve the management of multimorbidity.